(untitled) (Research, Society and Development, 2020)
The objective was to evaluate the production characteristics of kale leaf in a consortium with okra under organic management. The experiment was conducted in randomized blocks design with four replications. The treatments (T1 = three rows of kale with okra in between the lines, T2 = three rows of kale with okra every two lines, T3 = three rows of kale with okra thickened the lines, T4 = three rows of kale with okra thickened every two lines, T5 = kale monoculture, T6 = okra monoculture and T7 = okra dense monoculture). In monocultures the kale had okra spacing of 1.20 x 0.50 m between plants. The okra was thickened in plant spacing of 0.25 m. On kale leaf was evaluated the height, number of leaves, fresh and dry weight of leaves, leaf area, commercial and non-commercial productivity. For the okra was rated the height fresh weight of fruits per plant and productivity. It also calculated the efficiency rate of the earth (UET). All the consortiums presented UET above one with varied gains of 16 to 60% of productive efficiency.